STUDY OF THE EFFECT OF TEMPERATURE ON THE CONDUCTIVE PROPERTIES OF POLYMERIC COMPOSITE COATINGS - СВІСТІЛЬНІК, Р. Ф.; ПАТЛУН, Д. В. (Technologies and Engineering, 2024)
Purpose. Determination of the effect of temperature on the resistivity of composite coatings with different composition. Methodology. The surface electrical resistance was measured using the Kelvin method with a four-electrode cell. The temperature of the heating surface was measured using a resistive temperature sensor. The thickness of the composite coating layer was determined using a micrometer. Findings. The change in the value of the electrical resistivity of composite coatings in the temperature range of 30–120 °C was determined. The composite coatings with polymer matrices of nitrocellulose and bakelite resin show a negative temperature coefficient of resistance. The composite coating based on polyvinyl butyral has a positive coefficient of resistance, which indicates the suitability of such a system for use in heating elements. The influence of residual moisture on the properties of composite coatings based on polyvinyl butyral and bakelite resin was revealed. A significant increase in resistance and the release of low molecular weight compounds is observed, which necessitates preliminary heat treatment of the coatings before its use. The influence of the polymer matrix on the resistivity value is significant. The lowest value of resistivity is observed in the composition based on nitrocellulose. The highest values were found in compositions based on bakelite resin and a mixture of bakelite resin and polyvinyl butyral. Originality. The influence of temperature on the electrical characteristics of conductive coatings and the value of temperature coefficients of resistance was determined. Practical value. The influence of cyclic heating and the need for preliminary heat treatment of samples before use have been determined.